Technical Graphics Communication - R. Bertoline Gary (Mcgraw Hill, 2002)
In its third edition, Technical Graphics Communication,, has become a standard in the field of engineering and technical graphics. This text presents both traditional and modern approaches to technical graphics, providing engineering and technology students with a strong foundation in standard drafting practices and techniques. A strong emphasis on design and industry is found throughout, reinforcing the real and practical ways that technical graphics skills are used in real companies.